Changes and New Directions in Human Services : Selected conference proceedings of the 14th international Research Conference held at Luleå University of Technology, Human Work Science, October 2011 - Berg, Elisabeth (Luleå tekniska universitet, Arbetsvetenskap, 2011)
Preface This Conference, organised jointly by Staffordshire University, the University of East London and the University of Luleå, have so far provided a forum for policy, organisational and multidisciplinary critical analyses of the dilemmas facing the organisation and delivery of health, housing, education, social services and the human services generally. The theme of the conference 2010 was Changes and new directions in Human services. Change has been a leitmotif of the Human Services and the Public sector more generally in recent years; and whilst it is an aspect of all organizational, social political and economic life, it has been especially rapid and far reaching in the human services, exuberated by the turbulence and fall-out from the present to initiate further change in new directions. We accordingly invited papers that examine the responses of public, private and voluntary sector organisations and governments in tackling the contemporary problems facing human services related to the changes and new directions in service delivery and organisational effectiveness (locally, regionally and globally), as well as ethical and gender issues concerning access to labour market, equity and quality of service. This years Dilemmas Conference presents a selection of short papers from the conference. The articles highlight the changes and potential directions of society where wealth is undergoing a shift towards more explicitly neo-liberal society, where the private market takes over part of what has previously been state and local government responsibility which has consequences for people who are in need of social services. These changes affect the welfare state actors in organizations such as education, social work and also affect the employability of the general, and over time these changes can have significant consequences for welfare and social rights. Three of these articles, “The Financial Meltdown and the Crisis of Reproduction: Imaginations of Performance, Participation and Social Justice” by Brigitte ...